Relationship Between Knowledge and Level of Dietary Compliance In Patients with Hypertension - Iswatun Iswatun; Joko Susanto (Jurnal MIDPRO, 2021)
ABSTRACTHypertension is a disease that gets attention from all walks of life, considering that its impact requires comprehensive and integrated long-term treatment, one of which is to run a good diet. Hypertension is a natural way to control blood pressure. This study aims to determine the relationship between knowledge and the level of dietary compliance in patients with hypertension. The design of this study uses Analytical Correlation with a Cross-sectional approach. The samples obtained were 96 by using the purposive sampling technique. The independent variable is knowledge, the dependent variable is hypertension diet. The instrument used in this study was a questionnaire. Data tabulated and analyzed using the Spearmen Rank test with a significance level of <0.05. The result almost half of the respondents had less knowledge (43.8%), more than some who did not comply with their diet (58.3%). The test results obtained p = 0.000 (p <0.05). There is a relationship between knowledge and the level of dietary compliance in patients with hypertension. The participation of health workers is needed in increasing patient knowledge about hypertension diet so that patients can undergo a good diet. Keywords: Knowledge; diet compliance; hypertension.